The Dr. John Hall story: a case study in putative "Haunted People Syndrome". Issue 9 (21st October 2019) - O'Keeffe, Ciaran; Houran, James; Houran, Damien J.; Dagnall, Neil; Drinkwater, Kenneth; Sheridan, Lorraine; Laythe, Brian
ABSTRACT: Research suggests a "Haunted People Syndrome (HP-S)" defined by recurrent and systematic perceptions of anomalous subjective and objective anomalies. Such signs or symptoms are traditionally attributed to "spirits and the supernatural, " but these themes are hypothesised to morph to "surveillance and stalking" in reports of "group-(or gang) stalking, " We tested this premise with a quali-quantitative exercise that mapped group-stalking experiences from a published first-hand account to a Rasch measure of haunt-type anomalies. This comparison found significant agreement in the specific "signs or symptoms" of both phenomena. Meta-patterns likewise showed clear conceptual similarities between the phenomenology of haunts and group-stalking. Findings are consistent with the idea that both anomalous episodes involve the same, or similar, attentional or perceptual processes and thereby support the viability of the HP-S construct.